VD_FINDINFO PC 13/11 - 15/2012 vom 15. Juni 2012 - VD Tribunal cantonal (2012)
PRESTATION COMPLÉMENTAIRE, DROIT À LA PRESTATION D'ASSURANCE, REVENU DÉTERMINANT | 10 LPC, 11 LPC, 16 OPC-AVS/AI, 16a OPC-AVS/AI, 17 al. 1 OPC-AVS/AI